Pengaruh Profitabilitas dan Likuiditas terhadap Nilai Perusahaan yang Listing di Bursa Efek Indonesia - Tiara; Trisha Luvvent; Harini Vita Puteri; Jenny Novita Sari (Outline Publisher, 2024)
Telecommunication has become a vital aspect in society's day to day activities today. The development of Indonesia's telecommunication system lies in the hands of related companies, particularly those listed in the Indonesian stock exchange market. One method to determine the quality of a business is through identifying the value of a company. The value of a business may be influenced by factors such as profitability and liquidity. This research aims to analyze the impact of profitability and liquidity on the value of companies in the telecommunication sub-sector listed in the Indonesian Stock Exchange Market. This research was done using quantitative methods. The data is collected in the form of each company's annual financial reports from 2017 to 2021, taken from the company's official websites. The data is analyzed through formulas to calculate company value, profitability and liquidity. The results show that both profitability and liquidity has significant influence on company value.